Detection of Antimicrobial Drug Residues in Commercial Eggs Using Premi® Test - Kehinde , Omeiza Gabriel; Junaidu, Kabir; Mohammed, Mamman; AbdulRahman, Adeiza Musa (International Journal of Poultry Science, 2011)
Nigeria is one of the African nations with known reports of drug residue occurrence in tissues and matrices. Although the actual prevalence is not certain, previous studies have shown an increasing trend over time in the occurrence of antimicrobial drug residues. The current study was developed to further study the present status of occurrence of antimicrobial drug residues utilizing commercial eggs in the most centrally located state of the north central geopolitical zone, Nigeria. Other considerations investigated in the study include the possible roles of rapid expansion of unregistered small scale poultry (flock size) and management system on the occurrence of antimicrobial drug residues. Out of the total of 105 commercial farms randomly selected from 5 Local Government Areas (LGAs) of Kaduna State for the survey of antimicrobial usage, 92 (87.6%) used veterinary drugs frequently out of which 31.0% administered the drugs by self without adhering to veterinary recommendation. Further laboratory investigation showed a true occurrence of 7.6% residue out of the 1440 commercial eggs analyzed. Uncontrolled expansion of small scale/backyard farming and management system seemed to exert influence on the occurrence of antimicrobial drug residues.